PERANAN CO-CREATION PADA SME: SYSTEMATIC LITERATURE REVIEW - Pamungkas, Benni Ahdiyana (Unitri Press, 2024)
Small Medium Enterprise (SME) is the biggest supporter of a country's economy but generally has limited resources. For this reason, co-creation is important for SME to create shared value and become a competitive advantage. This study aims to reveal the state-of-the-art of the role of co-creation in SMEs. A systematic literature review was carried out using the PRISMA approach and a total of 15 articles were selected for review. SMEs are very diverse in terms of industrial sectors, technological needs, and positions spread across every corner of the country. The entire article shows that co-creation and collaboration between actors in the SME ecosystem functions to create a climate of mutually beneficial innovation for all parties.